Notes: Installation vs. Echelon Stock Policies for Multilevel Inventory Control - Axsäter, Sven; Rosling, Kaj (Management Science, 1993)
This paper compares installation and echelon stock policies for multilevel inventory control. The major results are for serial and assembly systems. For (Q, r)-rules, echelon stock policies are, in general, superior to installation stock policies. A Kanban-policy is identified as a restricted type of installation stock (Q, r)-policy.